2002
DOI: 10.1128/aem.68.5.2376-2381.2002
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella entericaInfections in Market Swine with and without Transport and Holding

Abstract: The objective of this study was to compare, by using identical sample types, the Salmonella enterica prevalences and serovar diversities between pigs necropsied on the farm and those necropsied at the abattoir after transport and holding. We necropsied 567 market weight pigs (>70 kg) from six herds. Pigs were alternately assigned to be necropsied on the farm or at the abattoir. One-half of the group was sent in clean, disinfected trailers to slaughter at a commercial abattoir. After transport (mean distance, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
143
3
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(163 citation statements)
references
References 23 publications
10
143
3
7
Order By: Relevance
“…The mean number of serovars isolated per batch also increased between the farm and the slaughterhouse. These phenomena have been previously reported by Hurd et al [15,16] and McKean et al [21], who hypothesised cross-contamination in lairage.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The mean number of serovars isolated per batch also increased between the farm and the slaughterhouse. These phenomena have been previously reported by Hurd et al [15,16] and McKean et al [21], who hypothesised cross-contamination in lairage.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, the lairage environment has been frequently found to be positive during the working day [31,38]. Whenever pigs waited in lairage at the slaughterhouse, an increase in the contamination rate was shown by studies which compared slaughtering on the farm and at the slaughterhouse [15,16]. A study carried out in 1987 also showed that contamination increased with the time spent in lairage, but the times compared (18 h, 42 h and 66 h) are very different from current reality [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, infected pigs do not exhibit clinical signs but do, however, shed Salmonella in their environment. They are then responsible for the contamination of susceptible pigs within the herd [7], during transport and lairage, and the contamination of carcasses during the slaughter process [4,14]. Focussing on reducing the number of Salmonella infected pigs at slaughter age can therefore lead to a reduction in pork food chain contamination 2 .…”
Section: Introductionmentioning
confidence: 99%